Implikasi Frasa “Turutilah Teladanku” Dalam 1 Korintus 4:16 Bagi Pembentukan - Erlina Zai; Elisua Hulu (Jurnal Missio Cristo, 2019)
An pattern is an example, an action that can be imitated by others, as Christ who is the main object becomes an example for humans, especially for those who know and experience Christ Himself, and who allow their minds to focus on Christ (Phil. 2:3- 9; 1:19-21a). Being an example is a must for Christians, just as Christ has been a role model for humans (believers), so Christians should be an example for everyone. Not only for believers, but for all non-Christians. A person can be said to be an example, someone whose actions, attitude, and character bear positive fruit according to the truth of God's Word.